Covering the Female Jewish Body. Dress and Dress Regulations in Early Modern Ashkenaz. (2nd January 2019) - Aust, Cornelia
ABSTRACT: Attempts to regulate, monitor, and sanction dress and outward appearance was a typical feature of the early modern period. Religious and secular authorities aimed at controlling its subjects' spending as well as the upkeep of estate boundaries. This development did not leave untouched Jewish society in central and east-central Europe. Internal Jewish sumptuary laws from the late sixteenth to the eighteenth centuries as well as moral literature were an attempt of the communal lay and religious elites to exercise control over the communities. Increasingly, dress ordinances pertained to women and moral writings of rabbis scolded women for their haughtiness and too lavish and expensive dress, especially for adapting non-Jewish styles of dress. This article explores these developments; and how the regulation of dress aimed also at gaining control over the female Jewish body.